Antibacterial activity of deodorant stick formula from ethyl acetate fraction of beluntas leaves (Pluchea indica L.) against Pseudomonas aeruginosa and Streptococcus pyogenes bacteria that cause body odor. - Yulis Adriana; Siva Fauziah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Beluntas contains flavonoids, tannins and steroids which can inhibit growth and reduce the risk of infection by microorganisms. Empirically, beluntas leaves are used by people to overcome unpleasant body odor, usually body odor is caused by the Pseudomonas aeruginosa and Streptococcus pyogenes. Stick deodorant is a cosmetic made from; sodium stearate (steric acid and sodium hydroxide) and as a solvent using propylene glycol. The aim of this research was to formulate the ethyl acetate fraction of beluntas leaves into a stick deodorant and test the antibacterial activity of Pseudomonas aeruginosa and Streptococcus pyogenes using the well diffusion method and test physical, chemical and quality parameters. microbiology. Stick deodorant were made into three formulations with different concentrations of the ethyl acetate fraction of beluntas leaves, namely Formula I with a concentration of 20%, Formula II is 30% and Formula III is 40% with the harding agent stearic acid: NaoH 10% (8.5:7.5). The quality test of the three formulation sticks deodorants met the requirements for pH test (range 6-7.0), homogeneity test, melting point test (range 55.40-60.9 Â°C), Microbiology test and water capacity test (aw). The results of the inhibition test against Streptococcus pyogenes were between 23.33-8.33 mm in the very strong inhibition category, the comparison deodorant had no inhibitory area and gentamycin 0.01% as a positive control had an inhibitory area of 29.66 mm in the very strong category. The inhibitory power against Pseudomonas aeruginosa is 11.5-18.92 mm in the strong inhibitory category, the comparison deodorant has no inhibitory area and 0.01% gentamycin as a positive control has inhibitory area of 21.66 mm in the very strong category.Keywords: Ethyl acetate fraction, stick deodorant, Pluchea indica.L, Pseudomonas aeruginosa, Streptococcus pyogenes, inhibition test